Pengaruh Metode Pembelajaran Mind Mapping Terhadap Pengetahuan Pada Kompetensi Dasar Menganalisis Dessert Melalui Pembelajaran Jarak Jauh - Azza Rusda Rusda; Rina Febriana Febriana; Guspri Devi Artanti (Ridwan Institute, 2022)
The application of various lecture methods through distance learning has several obstacles, so alternative methods are needed. This study aims to analyze the effect of mind mapping learning methods assisted by picture media on students' knowledge of the Basic Competence of Analyzing Dessert through Distance Learning. The research was held at Vocational High School 38 Jakarta with a population of 69 students in 2021/2022. The research method used a quasi-experimental, non-equivalent control group design with a purposive sampling technique. Class XI Culinary II is the Experiment Class with 33 Respondents, and Class XI Culinary I is the Control Class with 35 Respondents. Research data was sourced from the mean value of the post-test of the two classes. The results showed that the t-test = 2.138 with a significance of p = (0.037) <0.05. Accordingly, H0 was rejected, so Ha was accepted. The mean value of the Experimental Class showed an increase in knowledge of 22% while the Control Class was 14%. So, the mind mapping method with the help of image media is more influential in increasing knowledge of analyzing desserts through distance learning.